Understanding the impact of parental growth mindset on Chinese primary school students' mental health problems: the chain mediating effect of parenting self-efficacy and students' self-control - Yuan, Rong-Man (Frontiers in Psychology, 2026)
PurposeThe mental health of primary school students in China has garnered significant attention. Various factors can influence the mental health of primary school students, with family-related factors being particularly important. This study aims to explore the relationship between parental growth mindset and primary school students' mental health problems, as well as the longitudinal mediating mechanisms of parenting self-efficacy and students' self-control in this relationship. By providing theoretical support and practical guidance, this study aims to improve the mental health of primary school students.MethodsThis study utilized a three-wave longitudinal design spanning 1 year, recruiting students and parents from two primary schools in Beijing. Parental growth mindset (T1) and parenting self-efficacy (T2) were assessed via parent self-report using Parental Growth Mindset Scale and Parenting Self-Efficacy Scale. Students' self-control (T2) and mental health problems (T3) were assessed via student self-report using the Brief Self-Control Scale and the Strengths and Difficulties Questionnaire. Data were collected in three waves, resulting in 280 valid matched questionnaires.ResultsParental growth mindset significantly negatively predicted mental health problems in primary school students (β = −0.25, SE = 0.02, p < 0.001, 95% CI [−0.129, −0.049]). Parental growth mindset can influence mental health problems in primary school students through parenting self-efficacy (effect value = −0.09, 95% CI [−0.152, −0.036]), self-control (effect value = −0.04, 95% CI [−0.083, −0.005]), and chain mediating effects of parenting self-efficacy and students' self-control (effect value = −0.01, 95% CI [−0.030, −0.002]).ConclusionParenting self-efficacy and students' self-control play a chain mediating role between parental growth mindset and students' mental health problems in primary school students. This conclusion provides suggestions for improving mental health in primary school students.